Description of the Relationship between Learning Activities and Learning Outcomes of Training Participants at LPK Hoshi Hikari Parupuk Tabing Padang City - Febriansyah, Pradi Ciaca; 'Aini, Wirdatul (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This research was motivated by the low learning outcomes of the trainees atLPK Hoshi Hikari Parupuk Tabing, Padang City. This is presumably due to the lowactivity of the trainees resulting in low learning outcomes of the trainees. This studyaims to: 1) See an overview of the active learning of the training participants at LPKHoshi Hikari Parupuk Tabing, Padang City. 2) See an overview of the learningoutcomes of the training participants at LPK Hoshi Hikari Parupuk Parupuk Tabing,Padang City. 3) To determine the relationship between active learning and learningoutcomes of trainees at LPK Hoshi Hikari Parupuk Tabing, Padang City.This type of research is quantitative with this type of correlational research.The population in this study was 30 people and 21 people were taken as samples byusing stratified random sampling technique. Data collection techniques using aquestionnaire. Data analysis techniques use percentage formulas and rank orders.The results showed that: 1) the learning activity of the training participants atLPK Hoshi Hikari Parupuk Parupuk Tabing, Padang City was categorized as low; 2)The description of the learning outcomes of the training participants at LPK HoshiHikari Parupuk Tabing Padang City is categorized as low; 3) There is a significantrelationship between learning activity and the learning outcomes of the trainees atLPK Hoshi Hikari Parupuk Tabing, Padang City. Research suggestions are: 1) forinstructors to be able to innovate regarding learning activities so that it can be anattraction for training participants to be active in the learning carried out; 2) It ishoped that future researchers will be able to innovate and examine new variablesso that they can add to existing variables and complete them.